2015
DOI: 10.1177/1474704915593666
|View full text |Cite
|
Sign up to set email alerts
|

Health, Anticipated Partner Infidelity, and Jealousy in Men and Women

Abstract: Health has been identified as an important variable involved in mate choice. Unhealthy organisms are generally less able to provide reproductively important resources to partners and offspring and are more likely to pass on communicable disease. Research on human mate preferences has shown that both men and women prefer healthy mates. Yet to date, little research has examined how health relates to one's own mating experiences. In the present study, 164 participants (87 women) who were currently in heterosexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 82 publications
1
22
0
Order By: Relevance
“…Specifically, they found that individuals with more severe health problems reported more jealousy towards their partner and higher perceptions of potential infidelity on the part of their partner. These findings suggest that internal states of health and illness may have a multifaceted influence on mating behaviors, influencing personal sexual decisions (Griskevicius et al, 2011), as well as mate retention strategies (Arnocky, Pearson, & Vaillancourt, 2015).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Specifically, they found that individuals with more severe health problems reported more jealousy towards their partner and higher perceptions of potential infidelity on the part of their partner. These findings suggest that internal states of health and illness may have a multifaceted influence on mating behaviors, influencing personal sexual decisions (Griskevicius et al, 2011), as well as mate retention strategies (Arnocky, Pearson, & Vaillancourt, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…Thus, it is posited that an internal predictor, such as chronic and/or severe physical illness, can signal increased mortality risk, which fosters biobehavioral adaptation toward fast life history strategies, including maximizing short-term mating at the expense of longer-term parental investment (Hill, Boehm, & Prokosch, 2016;Waynforth, 2012). Arnocky, Pearson, & Vaillancourt (2015) provide compelling support for this internal prediction model, showing that an individual's history of illness can influence jealousy and perceptions of fidelity, important psychological correlates of fast life history sexual strategies. Specifically, they found that individuals with more severe health problems reported more jealousy towards their partner and higher perceptions of potential infidelity on the part of their partner.…”
Section: Introductionmentioning
confidence: 99%
“…Although some couples who experience infidelity may improve their primary relationship (e.g., Charny & Parnass, 1995; Olson et al, 2002), relational transgressions, such as a partner’s suspected betrayal, can have lingering negative consequences for many (Pederson & McLaren, 2017). Indeed, relationship distress and jealousy are associated with greater depressive symptoms (Riso et al, 2002), health problems (Arnocky et al, 2015), and alcohol and drug use (Buunk & Dijkstra, 2000). The stress of a partner’s recent infidelity is also associated with greater mental health symptoms, including depression and anxiety, and health-compromising behaviors (Shrout & Weigel, 2018).…”
Section: Suspected Infidelity and Transactional Stress Theorymentioning
confidence: 99%
“…We use transactional stress theory (Lazarus & Folkman, 1984, 1987) to investigate the degree to which people suspect a partner as being unfaithful and how that suspicion is related to appraisals of stress and reduced well-being. Evidence suggests that suspecting a partner of cheating is associated with harmful consequences for the individual, including frequency and severity of health problems (Arnocky et al, 2015), depression (Riso et al, 2002), and increased risky behavior such as alcohol and drug use (Buunk & Dijkstra, 2000). Such findings make studies on the mechanisms that link infidelity suspicion with negative outcomes all the more important.…”
mentioning
confidence: 99%
“…Marital infidelity is defined as the individual transition from a marital relationship by establishing a physical or emotional intimacy with a person outside the relationship. In other words, marital infidelity is a breach of contract in a relationship or any conduct that results in failures to perform any promises made by two persons [1]. Attitude toward marital infidelity can be indicative of the emotional and sexual infidelity of males or females to their spouses.…”
Section: Introductionmentioning
confidence: 99%